A case study on the design and development of solar food cooking system with a PCM as a heat storage unit. (18th March 2023) - Pawar, Usha; Bhole, Kiran S; Oza, Ankit; Panchal, Hitesh; Shah, Mohd Asif; Jaber, Mustafa Musa
Abstract: This study presents the design and fabrication of an urban solar food cooking system with a phase change material (PCM) as a heat storage tank. The effort has been taken to test the system experimentally and explore its thermal performance under actual climatic conditions of Mumbai, India. The solar heat energy is stored in the tank using commercial-grade erythritol as PCM in current research work. A heat exchanger is well designed and fabricated to regulate the flow of solar heat energy from the storage tank to the cooking vessel, similar to the domestic liquefied petroleum gas (LPG) cooking system. This solar cooker is designed to cook food twice a day for four family members (equivalent to an energy of 5000 KJ). Cooking experiments were conducted on 19 April 2019 for the afternoon and evening slots with rice and potato as cooking loads, respectively. The time taken for cooking rice and potato are from 12:30 pm to 12:52 pm (22 minute) and from 05:30 pm to 05:59 pm (29 minutes), respectively. The heat transfer rate was also observed at different storage tanks and cooking unit points. The experiments show cooking is possible twice a day and considered as convenient as domestic LPG stoves. Furthermore, it was found that comparatively less time was required for cooking food than other existing solar cookers.